1981
DOI: 10.1182/blood.v57.1.9.bloodjournal5719
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of graft rejection following bone marrow transplantation

Abstract: Bone marrow transplantation from an HLA-identical sibling is increasingly used in the treatment of severe aplastic anemia. One major problem with this approach is graft rejection that occurs in 25%-60% of patients conditioned for transplantation with cyclophosphamide. At most transplant centers it has been difficult to accurately identify patients at high risk for graft rejection. We studied a conditioning regimen of cyclophosphamide (200 mg per kg) and low-dose total body irradiation (3 Gy; equivalent to 300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Intravenous mesna 100 mg/kg/day was used as uroprotection. The total body irradiation dose was 300 cGy on day 1 for matched stem cell transplants [13] or 200 cGy twice a day on day 2~1 for mismatched or unrelated transplants [40]. Patients received granulocyte-colony stimulating factor 5 ug/kg subcutaneously beginning on day 1.…”
Section: Protocolmentioning
confidence: 99%
“…Intravenous mesna 100 mg/kg/day was used as uroprotection. The total body irradiation dose was 300 cGy on day 1 for matched stem cell transplants [13] or 200 cGy twice a day on day 2~1 for mismatched or unrelated transplants [40]. Patients received granulocyte-colony stimulating factor 5 ug/kg subcutaneously beginning on day 1.…”
Section: Protocolmentioning
confidence: 99%
“…Rejection was thought to result from the sensitization of patients to the minor histocompatibility antigens of donors induced by the previous blood product transfusion (22, 23). To reduce the risk of graft rejection, more intensive conditioning regimens which combine CY with other agents such as ATG, procarbazine or with radiation (24–28) and newly devised methods such as the addition of the donor's peripheral blood buffy‐coat cells to the marrow (29, 30) were developed. In 1983, Feig et al (27) showed encouraging results in this setting with a new conditioning regimen consisting of CY and TBI of 3 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…In the initial experiences of MSD-SCT using CY alone conditioning, high incidence of graft failure was a major challenge, particularly in previous heavily transfused patients [ 55 ]. Subsequently, MSD-SCT using radiation, including local-field and total-body irradiation (TBI), plus CY conditioning was attempted and resulted in a lower incidence of graft failure, but was associated with relatively higher incidences of long-term regimen-related morbidities and mortality [ 56 , 57 , 58 , 59 ]. Thereafter, several investigators attempted MSD-SCT using CY plus ATG conditioning, which might induce both effective immunoablation and lymphoablation [ 60 , 61 , 62 , 63 ].…”
Section: Allogeneic Sct For Patients With Saamentioning
confidence: 99%